2018
DOI: 10.1111/1346-8138.14198
|View full text |Cite
|
Sign up to set email alerts
|

Increased interleukin‐36γ expression in skin and sera of patients with atopic dermatitis and mycosis fungoides/Sézary syndrome

Abstract: Interleukin (IL)-36γ is expressed by keratinocytes and functions as a key initiator of inflammation in the skin. IL-36γ expression is enhanced by tumor necrosis factor-α and IL-17A, having a strong association with psoriasis. In this study, we examined the role of IL-36γ in atopic dermatitis (AD) and mycosis fungoides (MF)/Sézary syndrome (SS). Serum levels of IL-36γ in AD patients and MF/SS patients were elevated compared with those of healthy controls. Importantly, serum IL-36γ levels in AD patients positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 13 publications
3
16
0
Order By: Relevance
“…consequences, the data presented here may well provide a mechanistic link between the proteolytic activation of IL-36g by S. pyogenes SpeB and the initiation of guttate psoriasis (Nelson et al, 2011;Elliott, 1945). Published data have also shown that IL-36g is expressed in other inflammatory skin diseases associated with microbial infection including hydradenitis suppurative, eczema, and tinea, suggesting a potential causative role (Di Caprio et al, 2017;Hessam et al, 2018;Otobe et al, 2018). IL-36g is also upregulated in inflamed intestinal tissue as a result of stimulation from microbiota (Russell et al, 2016;Nishida et al, 2016).…”
Section: Discussionsupporting
confidence: 53%
“…consequences, the data presented here may well provide a mechanistic link between the proteolytic activation of IL-36g by S. pyogenes SpeB and the initiation of guttate psoriasis (Nelson et al, 2011;Elliott, 1945). Published data have also shown that IL-36g is expressed in other inflammatory skin diseases associated with microbial infection including hydradenitis suppurative, eczema, and tinea, suggesting a potential causative role (Di Caprio et al, 2017;Hessam et al, 2018;Otobe et al, 2018). IL-36g is also upregulated in inflamed intestinal tissue as a result of stimulation from microbiota (Russell et al, 2016;Nishida et al, 2016).…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, expression of IL‐36γ in keratinocytes is induced by scratching in an in vitro Koebner model 43 . Recent studies suggest that IL‐36γ could be important in the pathogenesis of AD as IL‐36γ was found highly expressed in keratinocytes, especially in the upper epidermal layers, 44 and IL‐36γ is elevated in acute AD, and further increased in chronic eczematous lesions 31 . A biological drug against IL‐36γ has already been tested in pustular psoriasis with promising results 45 …”
Section: Discussionmentioning
confidence: 99%
“…46 One study has reported increased IL-36 expression in MF/SS patients. 47 Aside from being a diagnostic adjunct, the use of IL-36 staining for directing therapy is currently being investigated. IL-36 inhibition has been shown to decrease acanthosis and scale thickness in mice that received IL36-R blocking antibody.…”
Section: Discussionmentioning
confidence: 99%